The Criticism of Vytautas Kubilius and Rimvydas Šilbajoris and the Ghost of Deconstruction - Jurgutienė, Aušra (Colloquia, 2016)
The author of this article discusses sypmtoms of deconstruction in the texts of two famous Lithuanian critics of the second half of the twentieth century: Vytautas Kubilius and Rimvydas Šilbajoris. She asserts that while Kubilius was noted for his phenomenological interest in the writer’s stylistic uniqueness and Šilbajoris’s criticism drew on theories of Formalism and Reader Response (even though both sought maximum identification with and truth in the text, essentialistically believing that its artistic quality is determined by an organic and structurally coherent unity of content and form), both of their texts contain some elements related to the theory of deconstruction. The first and most important symptom is each critic’s change in view from history to the text’s language and its immanence. The author relates the second symptom of deconstruction with ideas of genre synthesis, methodological eclecticism, their essayistic writing, and the erasure of the divide between literary and academic language, rational and emotional criticism. The third symptom of deconstruction is lifted from these critics’ connections with the Romantic tradition, which is marked by the “synthesis” of the idealism–nihilism opposition and the ideas around the figurative nature of language, its undefined and playful qualities.